Pengaruh Iklan, Public Relations, Direct dan Online Marketing Terhadap Keputusan Pembelian Properti di Depok - Siti Nurafiah (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
This study aims to analyze the effect of advertising, public relations, direct and online marketing on property purchasing decisions in Depok. The data collection method uses purposive sampling, where the sample criteria for this study are property consumers in Depok City who have bought housing in the last 5 (five) years. From the results of distributing the questionnaires during October - November 2022, 90 data were collected from respondents who deserved further processing. The data that has been collected was processed using multiple linear regression with SPSS software version 26.00. The results of the study show that advertising has no significant effect on purchasing decisions. According to respondents, even though there are advertisements that they see on the street, because in general developers use banners, this does not influence them in making decisions to buy housing in Depok, because most of the respondents belong to a group of customers who do not pay attention to the advertisements that appear on the road. The results showed that public relations had a significant effect on purchasing decisions, then, direct and online marketing had a significant effect on purchasing decisions, together with advertising, public relations and direct and online marketing had a significant effect on purchasing decisions